The conduction velocity of slower and the fastest fibres in infancy and childhood. - Hakamada, S (1982)
Motor nerve conduction velocity of the ulnar nerve was measured in 54 infants of various ages. Conduction velocity of slower fibres was measured using Hopf's technique, and maximal conduction velocity was measured with the usual method. Both maximal conduction velocity and conduction velocity of slower fibres increased with maturation. The former was about 65 m/s at the age of about 3-5 years, but thereafter it decreased slightly to about 60 m/s. Conduction velocity of slower fibres increased gradually until about 3 or 4 years of age, and then ranged about 40-50 m/s. The difference between the two velocities increased until 7 or 9 months of age; during the next 8 years, it tended to decrease to about 8-16 m/s. The increasing difference in size between the largest and the smallest myelinated fibres with maturation correlated with the developmental increase of the difference between maximal conduction velocity and conduction velocity of slower fibres. The anatomical evidence of the slight decrease of the axon diameter of the large fibres at the age of 7-14 years may correspond to the slight reduction of maximal conduction velocity after about 5 years of age.